Scheduling of combined continuous and discrete-event simulation models on multiprocessors - Strydom, O. M.(Otto Marsel) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1995.